Pengaruh Faktor Motivasi Peran Serta Kader dan Masyarakat Dalam Kegiatan Posyandu di Kabupaten Kuningan - Rossi Suparman (Jurnal Ilmu Kesehatan Bhakti Husada: Health Sciences Journal, 2012)
Introduction: One from of the most common Society Resourced Health Efforts was Posyandu. Management of Posyandu’s activities depends on the cadress and communities who run it. Cadres adnd communities participation were well influenced by motivation factor that they owned.This study was aimed to analyze the influence and differences of motivation factors and also which motivation factor was the most influence to the participation of cadres and communities in posyandu activities. Method: The method was explanatory survey with cross sectional study using questioner. Total samples were 300 respondents, which include 100 active cadres and 100 no active cadres. These samples were taken by simplified random sampling. Other samples, which are 100 communities respondent who was taken by purposive sampling. Ordinal data resulted from this study is transformed to interval data by Successive Interval Method, and then analyzed. Two analysis methods used in this study are descriptive statistic analysis and inductive statistic analysis. The inductive analysis used Structural Equation Modeling (SEM). Results: The results showed that motivation factor have influence to the participation of cadres and community in posyandu. External motivation factor for overall cadres and community and also active cadres have more significant influence compare to internal motivation factor. While in no active cadres the situation is in opposite. Community showe nonsignificant result in the influence of both motivation factors. The most significant indicator for internal motivation in cadres and community is the sense of responsibility, as for external motivation factor is social relationship. If these were separated, there will be a different influence in each group. The most significant indicator for internal motivation factor: in active cadres is reward, nonactive cadres was achievement, and community was the sence of responsibility. Whilst for external motivation factor, the social relationship is the most significant indicator in the three groups. As the conclusion, motivation factor model influential to the participation of cadres and communities in posyandu activities. These may be developed as one of intervention reference to the cadres and communities in order to increase the posyandu existense so in the end will enhanced the communities health level.